4. The degree of motor cortex excitability in migraine depends on the days elapsed since the last attack. Issue 12 (December 2016) - Bracaglia, M.; Coppola, G.; Napoli, F.; Di Lenola, D.; Serrao, M.; Di Lorenzo, C.; Pierelli, F.
Abstract : Here, we investigated whether level of cortical excitability changes with the distance from the last migraine attack could explain previous inconsistent results. Twenty-six patients with untreated migraine without aura (MO) underwent MEP study between attacks and were compared to a group of 24 healthy volunteers (HV). The TMS figure-of-eight coil was positioned over the left motor area. We first identified the resting motor threshold (RMT) and then amplitude of MEP was evaluated by delivering and averaging 10 single pulses of TMS using a stimulus intensity of 120% RMT at a rate of 0.1 Hz. Mean RMTs (54.2 in MO vs. 55.8 in HV) and MEP amplitudes (3057 microV in MO vs. 3675 microV in HV) were not significantly different between MO and HV. In MO, the RMT negatively correlated with days elapsed since the last migraine attack ( r  = −0.426, p = 0.03), i.e. RMT was minimal at a long time interval after an attack while it was greater and within the range of normative values approaching to an attack. The dynamic RMT variations found here resemble those we have previously reported for visual and somatosensory evoked potentials, and may represent time-dependent plastic changes in brain excitability in relation with the migraine cycle.